Wystawy historyczne realizowane przez zielonogórskie muzeum w latach 1960-1989 = Historical exhibitions realised by the Museum of Zielona Góra, 1960-1989 - Cincio, Arkadiusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article shows the exhibition of District Museum in Zielona Góra in the range of displays chich introduce and popularise regional history, the history of Poland and general history from 1960-1989. On the one hand, this period is defined by the beginning of a regular exhibition activity in the present headquarters, but on the other hand it is specified by the start of system transformations.
Keywords: Muzeum Ziemi Lubuskiej; wystawa; historia; po 1944 r.